Peran dan Strategi Lembaga Swadaya Masyarakat dalam Pemberdayaan Sosial Ekonomi Masyarakat (Studi Kasus di Kabupaten Manggarai Nusa Tenggara Timur) - Ngalu, Rudolof; Jamun, Yohannes Marryono; Wejang, Heronimus Emilianus Arjono (Babes Litbang Yankessos, 2019)
This paper was conducted to examine the role and strategy of NGOs in the socio-economic empowerment of communities in Manggarai Regency. This study was motivated by concerns about poverty which have become an acute problem in this area. Although various types of government social assistance programs continue to be rolled out and the development paradigm has shifted from a centralized to a decentralized system, the poverty rate remains relatively high. In the midst of this condition, the presence of NGOs is an alternative option and hope. The research used qualitative approaches and case study methods. Data collection was done through interviews and document studies. Data analysis used the Miles and Huberman models which consist of data display, data reduction, and conclusion drawing. The results of the study showed that NGOs in Manggarai Regency has carried out the role of community empowerment in the socio-economic field. The strategies developed by NGOs generally include (1) group-based approaches, (2) changing ways of thinking, (3) participation and capacity building, (4) institutional strengthening for long-term independency. While the challenges encountered by NGOs in carrying out their roles were: (1) minimal capacity of NGO personnel, (2) the lack of institutional capacity in analyzing situations and needs, (3) wrong mindset of society and (4) partnerships with governments that are too bureaucratic..Â